Defoliation of Soybean Expressing Cry1Ac by Lepidopteran Pests - María G. Murúa; Martín A. Vera; María I. Herrero; Sofia V. Fogliata; Andrew Michel (Insects, 2018)
Lepidoptera, stink bugs, and weevils are important pests in soybean. For lepidopteran control, insecticides and seed treatments are used. As an alternative, Bt soybean was developed to control primary pests of Lepidoptera such as Rachiplusia nu (Guenée) (Noctuidae), Chrysodeixisincludens (Walker) (Noctuidae), Anticarsia gemmatalis Hübner (Erebidae), Helicoverpa gelotopoeon (Dyar) (Noctuidae), and Crocidosema aporema (Walsingham) (Tortricidae). However, the use of transgenic plants, and the resulting reduction of insecticide against target pests, may allow other pest species to become more prevalent in agricultural environments. Soybean expressing Cry1Ac against different lepidopteran nontarget and target insect pests was evaluated, and its performance was compared with non-Bt soybean with seed treatment. The treatments were Bt soybean, non-Bt soybean with seed treatment (Fortenza® diamide insecticide, Syngenta, Buenos Aires, Argentina), and non-Bt soybean without seed treatment. Larvae of H. gelotopoeon, Spodoptera albula (Walker) (Noctuidae), Spodoptera cosmiodes (Walker) (Noctuidae), Spodoptera eridania (Stoll) (Noctuidae), and Spodoptera frugiperda (J. E. Smith) (Lep.: Noctuidae) were used. The plants of each treatment were infested with larvae of each species, and the percentage of leaf damage produced by each species was recorded. The results showed that Bt soybean provided control of H. gelotopoeon and had a suppressive effect on S. frugiperda and S. albula. However, S. eridania and S. cosmiodes were not susceptible to the Cry1Ac protein in MON 87701 × MON 89788 soybean when evaluated by greenhouse infestation. Considering the performance of each species using non-Bt soybean without seed treatment, S. eridania would represent a potential risk in soybean crops.